Manifestations of the Catholic Modernism in Lithuania - Pruskus, Valdas (Problemos, 1988)
The origination of the modernistic ideas among the liberal Lithuanian catholic clergy and intellectuals in the end of 19th century and in the beginning of the 20th century are considered. The criticism of blind dogmatism, of primitive and formal religiosity, the fight for the ideas of national religious art (J. Šlapelis), for the evolutionary development of society (S. Šulte) and religion (Derkintis), as well as the quest for the new forms of religious rite (A. Jakštas) are being analysed. The modernists strived for the emancipation of the Lithuanian Catholic Church from archaic relics, inertion and from the patronage of the Polish clergy. Their propagation of tolerance and authentic thinking has paved the way for the Lithuanian modernism after World War I.